Akibat Hukum Peralihan Hak Atas Tanah Milik Anak Tanpa Persetujuan Penetapan Perwalian dari Pengadilan (Studi Putusan Pengadilan Negeri Malang No. 217/Pdt.G/2017/PN.Mlg) - Wendi Yoanda (CERED Indonesia, 2020)
This study uses a statutory approach and a case approach. This type of juridical-normative research is descriptive analysis. Data sourced from secondary data. Data collection techniques using library research techniques with document study data collection tools (document study). Qualitative data analysis by drawing conclusions inductively. The results of the study indicate that: The legal arrangement for the transfer of rights to children's land is regulated in Article 393 of the Civil Code; The legal consequences of the transfer of land rights owned by children without consent the determination of the guardianship of children from the court caused the transfer of land rights to be legally flawed, so that it could be canceled; and transfer of children's rights to land without stipulation of guardianship of the child in Malang District Court Decision No. 217 there has been clear consideration and legal construction in accordance with applicable legal provisions.